Perdas de nutrientes e sedimento por erosão e seus efeitos na qualidade da água - Paula, Daniela Tolêdo de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The preparation of the soil, the presence or absence of vegetation, as well as the proportion of this cover soil can influence the quantities of organic matter and nutrients lost by erosion, hence the preservation of the quality of soil and water. For the above, this study aimed to evaluate nutrient losses by erosion and its effects on water quality in area with cane sugar cultivation us conventional and conservation tillage systems. In experiment 1 the experimental area is located in Guariba - SP, the same soil was classified as red-yellow dystrophic oxisol. The experimental design was completely randomized in a factorial design, 5 treatments with straw cane sugar and 3 repetitions, totaling 15 plots . In the treatments, the straw was manually distributed across the surface of the soil in amounts of 0 ; 0.157 ; 0.35; 0.515 and 0.7 kg, providing roofing 0% (CS0), 25% (CS25), 50% (CS50), 75% (CS75) and 100% (CS100), respectively. The experimental plots were subjected to simulated rain with average intensity of 60 mm h -1 for 65 minutes. It was observed that with increasing soil erosion losses in rill, there is an increase in clay content of the sediment. This fact is directly linked to greater or lesser coverage provided to the soil. There is the need for minimum ground cover of 42 % so there is no enrichment rate (ER) of the sediment eroded by Psed, Pads and clay. The experiment experimental area 2 is located in Pradópolis - SP, in a soil oxisol clayey, which was in time of renewal of cane sugar cultivation. Three tillage systems were used. The experimental plots were subjected to simulated rain with medium intensity around 65 mm h-1 for 75 minutes. In preparing located, as there is greater ground cover, soil loss is much lower than in conventional and reduced. Conventional treatment had higher losses of OM, P, K, Ca and Mg in the sediment. The concentrations of K and P in runoff water can be considered critical for purposes ...

O preparo do solo, a ausência ou presença de cobertura vegetal, bem como a percentagem de cobertura presente no solo, podem influenciar nas quantidades de matéria orgânica e nutrientes perdidos pela erosão, consequentemente na conservação da qualidade do solo e da água. Pelo exposto, este estudo teve como objetivo avaliar as perdas de nutrientes por erosão e seus efeitos na qualidade da água, em área com cultivo de cana-de-açúcar nos sistemas de manejo convencional e conservacionista. No experimento 1 a área experimental localiza-se em Guariba - SP, em solo classificado como Latossolo Vermelho-Amarelo distrófico. O delineamento experimental foi o inteiramente casualizado num esquema fatorial, 5 tratamentos com palha de cana-de-açúcar e 3 repetições, totalizando 15 parcelas. Nos tratamentos, a palha foi manualmente distribuída em toda a superfície do solo, nas quantidades de 0; 0,157; 0,35; 0,515 e 0,7 kg, proporcionando coberturas de 0% (CS0), 25% (CS25), 50% (CS50), 75% (CS75) e 100% (CS100), respectivamente. As parcelas experimentais foram submetidas a chuvas simuladas com intensidades médias de 60 mm h-1, durante 65 minutos. Observou-se que com o aumento das perdas de solo por erosão em entressulcos, há incremento no teor de argila do sedimento erodido. Tal fato está diretamente ligado à maior ou menor cobertura oferecida ao solo. Há a necessidade da cobertura do solo mínima de 42% para que não haja taxa de enriquecimento (ER) do sedimento erodido, por fósforo (Psed e Pads) e argila. A área experimental do experimento 2 localiza-se em Pradópolis - SP, em um Latossolo Vermelho eutroférrico textura muito argilosa, a qual encontrava-se em época de renovação do cultivo de cana-de-açúcar. Foram utilizados três sistemas de preparo do solo. As parcelas experimentais foram submetidas a chuvas simuladas com intensidade média em torno de 65 mm h-1, durante 75 minutos. No preparo localizado, como há...
Keywords: Cana-de-açúcar; Latossolos; Água - Qualidade; Nutrientes; Erosão